Museu, templo de sabedoria: do restauro as oportunidades de educação patrimonial por meio da coleção numismática do museu histórico e cultural de arraias - Silva, Léa Coimbra (Universidade Federal do Tocantins, 2021)
Museums develop an important pedagogical role through their Heritage Education actions and activities, making it a true temple of wisdom. In this sense, the general objective of this Technical Scientific Report is to present the activities that involved the restoration, hygiene, identification and storage of the Numismatic Collection of the do Museu Histórico e Cultural de Arraias - MHCA, from the perspective of the relations between Museums and Heritage Education. The methodological procedures adopted were based on applied and exploratory qualitative research, bibliographic, documentary research and action research. The presentation of the results demonstrated the relevance of the work developed and the various possibilities of actions that the Museum can develop using its collection, especially the numismatic collections such as the one that was the object of this work and that is now organized, identified and available for various actions of heritage education. In addition, the work points to the possibility of developing other research based on the MHCA collection, becoming an incentive for knowledge, asserting as a space for incentive and knowledge production.